Distinct aspects of pain catastrophizing according to chronic pain syndromes - Zortea, Maxciel; Antunes, Luciana da Conceição; Segabinazi, Joice Dickel; Serrano, Gerardo Beltran; Elkfury, Jéssica Lorenzzi; Carvalho, Fabiana; Santos, Vinicius Souza; Caumo, Wolnei (Clinical and Biomedical Research, 2018)
Introduction: Catastrophizing is the tendency to magnify the threat value of pain and has been associated with measures of physical and psychological disability among individuals with several pain conditions. The aim of this study was to investigate whether pain catastrophizing is differentially associated with distinct pain syndromes. Methods: This is a cross-sectional study including 158 patients (40 with fibromyalgia, 25 with myofascial pain syndrome, 33 with chronic tensional type headache, 33 with endometriosis, and 27 with knee osteoarthritis) and 93 healthy subjects. The recruitment procedure occurred in concurrence with randomized controlled trials. Participants answered the following instruments: Brazilian Portuguese Pain-Catastrophizing Scale, Beck Depression Inventory II, State-Trait Anxiety Inventory, Pittsburgh Sleep Quality Index, visual analogue scale for pain, as well as a sociodemographic questionnaire. Results: For the total pain catastrophizing score, patients with endometriosis had significantly more catastrophizing thoughts than knee osteoarthritis (p < 0.05). Healthy participants had lower scores than any clinical group. More interestingly were the dimensions of pain catastrophizing, which showed significant differences in more than two groups, especially magnification scores, since these scores were able to discriminate, in a particular way, the majority of clinical samples from each other. We also observed differences between rumination, magnification and helplessness scores in all groups, suggesting that the characteristics of pain catastrophizing are distinct according to the pain disorder. Conclusions: The results suggest that dimensions of pain catastrophizing differ between pain syndromes. Therefore, it is important that researchers and clinicians focus on cognitive and emotional aspects of pain perception to have more successful interventions. Keywords: Chronic pain; catastrophizing; cross-sectional study